Pemanfaatan Tanaman Obat oleh Masyarakat Sekitar Kawasan Hutan Koa, Desa Linamnutu, Kecamatan Amanuban Selatan, Kabupaten Timor Tengah Selatan - Aderia Wewo; Ludji Michael Riwu Kaho; Astin Elise Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This study was conducted to determine the types of medicinal plants, and how to process the medicinal plants whice used by the community around the Koa Forets, Linamnutu Village, South of Amanuban Districts, South Central Timor Regency. This research was conducted from November 2019 to October 2019. This research was conducted with qualitative descriptive data collection techiques, with primary data in the form of interview, observations and documentation. The data processing stage is carnied out by compiling, identification, classification and data analysis the parts of the plant used, presentation of parts used, how to concoch and how to use. The result of the study and the result of interview with respondents showed that there were is thypes of medicinal plants used by community around the Koa Forest, Linamnutu Village, South of Amanuban Districts, South Central Timor Regency.Thypes of medicinal plants consist of Bunga Putih/Sufmuti (chromolaena odorata L. ), Mahoni ( Swietenia mahagoni ), Kesambi/ Usapi(schleicheraoleosa), JambuBiji ( Psidium guajava L.), Atta/ Srikaya (Annona Squamosa), PariaHutan(Momordica balsamina), Sambiloto (Andrographis paniculata), Marungga/Kelor (Moringa oleifera), Flolo/ Faloak ( Sterculia quadrifida) Alang-Alang (Impereta cylindrical), Kayu Merah (Pinus Sylvestris), Delima(Punica granatum), Kiu/ Asam (Tamarindus indica), Feu / Kemiri (Aleurites moluccana), and Damar (Agathis dammara). Medicinal plants parts whice used were Leaf, Fruits, Seed, Outher shell, Sap, and Root and the highest usage presentation is on the leaf of plant that is 32% and the lowest presentation was in the sap part that is 4 %. The process of making medicine is still using a simple method, that is : pound or grind and boil with water. While the method of using the medicinal plans is to be smeared or sprinkled on the part that hurts, Or drink and consumed directly.